Electrophysiologic Study of Cognitive Functions in Epileptic Patients - Mohammed, Shaymaa J.; Al-Madfai, Zaid; Al-Owath, Mazin M. H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Cognitive dysfunctions in epileptic patients may develop due to the neurophysiologic changes related to seizures or antiepileptic drugs.Objectives: The aim of this longitudinal study was to evaluate the cognitive dysfunction in epileptic patients under antiepileptic drug therapy by the aid of event related potentials.Patients & Method: P300 latencies were obtained from Fz, Cz and Pz electrodes positions from both epileptic patients (n = 224) and age and sex matched control group (n = 91). Epileptic patients were classified either having partial epilepsy, generalized epilepsy or both partial and generalized epilepsy (combined epilepsy). EEG and p300 test repeated for each patient every three months for one year. The effect of epilepsy type and duration, treatment types (monotherapy/ polytherapy), daily dosages and EEG abnormalities on P300 latencies were studied.Results: P300 latencies were longer in the epileptics when compared to controls (P < 0.05). Besides, our results pointed out that P300 latencies were longer in patients with generalized and combined epilepsy as compared to those with partial epilepsy (P < 0.05).Conclusion: We believe that P300 latencies may have an important role in the evaluation of cognitive dysfunction in epileptic patients treated with antiepileptic drugs.